Factors influencing mutual support among older people in China: a cross-sectional study - Xu, Lichun; Lin, Liyu; Huang, Xiaojin; Guan, Aixuan; Cheng, Lianfang; Zheng, Yicen; Zhang, Shuyi (Frontiers in Public Health, 2025)
AimsTo investigate the willingness of Xiamen’s older adult community members to participate in mutual support for the older adult, and to explore the factors that influence their willingness to participate.BackgroundMutual support in old age care fully respects the autonomy and initiative of the older adult, and has become a practical option for solving the problem of mutual support in old age in China. This study investigates the willingness of Xiamen’s older adult community members to participate in mutual support and scientifically examines the influencing factors behind this willingness.MethodsThis is a cross-sectional study that collected data from September 2023 to January 2024. The study population consisted of 502 older adult people from Xiamen, China, selected using a convenience sampling method. A self-designed questionnaire was used to conduct the survey. Binary logistic stepwise regression analysis was used to determine the influencing factors.ResultsThe binary logistic stepwise regression analyses showed that being in a community that regularly organizes activities for the older adult, occasionally participating in community-organized activities for the older adult, being willing to accept help from other older adult people, being willing to provide help to other older adult people, and not living alone were more likely to participate in mutual support.ConclusionThe government and community organizations should play a role in guiding and safeguarding policies, while also strengthening the promotion of mutual support within the community. Additionally, they should provide targeted and demand-driven mutual support services for the older adult, promoting sustainable and healthy development of mutual support for older people to improve their quality of life and well-being.